Prevalence of colonic polyp and its predictors in patients with acromegaly - Purnima Agarwal; Praveer Rai; Manoj Jain; Shambhavi Mishra; Uttam Singh; Sushil Kumar Gupta (Indian Journal of Endocrinology and Metabolism, 2016)
Background: There are conflicting data regarding the prevalence of colorectal polyp in patients with acromegaly. Subjects and Methods: Consecutive forty-seven acromegalic patients (21 men, 26 women), with a mean age of (40 ± 12 years) attending endocrinology outpatient department underwent full colonoscopy. All the patients underwent clinical and biochemical evaluation (glucose suppressed growth hormone (GH), Insulin-like growth factor-1 [IGF-1], fasting insulin, and glucose). The control group (n = 120) for colonoscopy was adult subjects undergoing evaluation for symptoms of irritable bowel syndrome. Clinical and biochemical parameters in acromegalic patients with colonic polyp were compared to those without a polyp. Results: Patients with acromegaly had significantly higher prevalence of colonic polyp as compared to control subjects (10.6% vs. 0.8%). None of the patients with polyp had skin tags. There was no significant difference between subjects with and without colonic polyp in duration of illness, basal, and glucose-suppressed GH and most recent IGF-1. Fasting blood sugar was significantly higher (P < 0.05) in adenoma group after adjusting for age, body mass index (BMI), and insulin levels. Patients in adenoma group showed a trend toward male gender and younger age as compared to those without adenoma. Conclusions: Subjects with acromegaly as compared to control have a higher prevalence of colonic polyps. There was no association of polyps seen with age, BMI, skin tags, homeostasis model assessment of insulin resistance index, duration of disease, and basal and glucose-suppressed GH and IGF-1 levels. There were no specific predictive factors detected. Screening full colonoscopy is recommended in all cases with acromegaly.